Pseudopterosin A-D Modulates Dendritic Cell Activation in Skin Sensitization - Johanna Maria Hölken; Katja Friedrich; Russel Kerr; Nicole Elisabeth Teusch (Marine Drugs, 2025)
This study investigates the anti-inflammatory effects of the marine diterpene glycosides pseudopterosin A-D (PsA-D) in mitigating nickel sulfate (NiSO4)-induced skin sensitization. In dermal dendritic cell (DDC) surrogates, PsA-D pre-treatment significantly reduced NiSO4-induced upregulation of key activation surface markers, cluster of differentiation (CD)54 (~1.2-fold), and CD86 (~1.6-fold). Additionally, PsA-D inhibited the NiSO4-induced activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway by suppressing inhibitor of kappa B alpha (IκBα) degradation. Furthermore, PsA-D suppressed inflammatory responses by inhibiting the NiSO4-induced secretion of pro-inflammatory cytokines, including interleukin (IL)-8 (~6.8-fold), IL-6 (~2.2-fold), and IL-1β (~5.3-fold). In a full-thickness human skin model incorporating DDC surrogates, topical application of PsA-D effectively attenuated NiSO4-induced mRNA expression of IL-8 (~2.1-fold), IL-6 (~2.6-fold), and IL-1β (~2.2-fold), along with the key inflammatory mediators cyclooxygenase-2 (COX-2) (~3.5-fold) and NOD-like receptor family pyrin domain-containing 3 (NLRP3) (~2.1-fold). Overall, PsA-D demonstrated comparable efficacy to dexamethasone, a benchmark corticosteroid, providing a promising therapeutic alternative to corticosteroids for the treatment of skin sensitization and allergic contact dermatitis. However, to maximize PsA-D’s therapeutic potential, future studies on optimizing the bioavailability and formulation of PsA-D are required.